International Symposium on Oilfield Chemistry 2007
DOI: 10.2118/105485-ms
|View full text |Cite
|
Sign up to set email alerts
|

Water-Based Drilling Fluid for HT/HP Applications

Abstract: The superior performance of invert emulsion fluids in challenging drilling operations such as HT/HP wells makes them the preferred fluid for such applications. However, there are instances such as drilling in environmentally sensitive areas, or where costs and logistics become prohibitive, where their use is undesirable. In such circumstances, a high-performance water-based drilling fluid is the only option available. A main challenge in developing a water-based fluid for such applications has been to maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Mn 3 O 4 provides low rheological properties and equivalent antisag behaviour (Kleverlaan and Lawless 2004;Carbajal et al 2009). Tehrani et al (2007) noticed that Mn 3 O 4 -based drilling fluid might undergo a degree of flocculation and produce higher plastic viscosity values upon heat aging. To avoid agglomeration of Mn 3 O 4 particles at high temperatures, Mu et al (2006) suggested synthesizing Mn 3 O 4 particles using H 2 O 2 as an oxidant and starch as a capping agent.…”
Section: Weighting Agents In Drilling Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mn 3 O 4 provides low rheological properties and equivalent antisag behaviour (Kleverlaan and Lawless 2004;Carbajal et al 2009). Tehrani et al (2007) noticed that Mn 3 O 4 -based drilling fluid might undergo a degree of flocculation and produce higher plastic viscosity values upon heat aging. To avoid agglomeration of Mn 3 O 4 particles at high temperatures, Mu et al (2006) suggested synthesizing Mn 3 O 4 particles using H 2 O 2 as an oxidant and starch as a capping agent.…”
Section: Weighting Agents In Drilling Fluidsmentioning
confidence: 99%
“…They also compared formation damage by solids invasion in various drilling fluids, including Mn 3 O 4 -based fluids. However, it is reported that Mn 3 O 4 particles aggregate up to 20 lm in aqueous and oil-based fluids (Svendsen et al 1995;Tehrani et al 2007). Accumulation of these aggregates in the critical near-wellbore region is not desirable, and can result in stuck pipe during drilling operations.…”
Section: Formation Damage By Mn 3 O 4 Drilling Fluidsmentioning
confidence: 99%
“…Thus, the prepared nanofluids added in drilling mud will yield benefits in stabilizing the viscosity and in cooling the drilling mud. It is worth noting that researchers at the National Energy Technology Laboratory are designing an environment-friendly nanofluid for oil and gas exploration and drilling that can withstand the high temperatures, as well as the highly-toxic, corrosive hydrogen sulfide gas that diffuses into drilling fluids in deep and horizontal wells during drilling operations (Tran and Lyons 2007). Their study indicated that there is a need for the development of novel nanofluids for drilling-fluid design to satisfy various operational requirements.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] There have been extensive researches reported by many institutions on the development of such high performance drilling fluids. 1,[5][6][7][8] Although we are conducting research and development on a range of novel drilling fluid additives for these demanding applications, a synthetic rheology modifier is the focus of this presentation.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11] Polyelectrolyte-type rheology modifiers, however, can provide much better thermal stability, often possess poor shear-thinning properties and are sensitive to salt and drill solids with high plastic viscosities and shear degradation. 1 A desired rheology modifier for HTHP drilling should possess similar rheological properties to xanthan gum (e.g., high shear thinning) with enhanced salt tolerance and thermal stability. A high degree of shear-thinning and excellent suspension power of the weighting agents are key requirements in developing the new class of synthetic rheology modifier.…”
Section: Introductionmentioning
confidence: 99%